ChemInform Abstract: The First Example of an Unusual Rearrangement in the van Leusen Imidazole Synthesis. Issue 17 (April 2016) - Fodili, Mokhtar; Nedjar‐Kolli, Bellara; Vedrenne, Marc; Saffon‐Merceron, Nathalie; Lherbet, Christian; Hoffmann, Pascal
Abstract: The imidazole ring system (V) can be prepared by reaction of TosMIC (IV) with a tautomeric enamine form (III) of a secondary ketimine.